(untitled) (Innovative Teaching and Learning Journal, 2023)
This mini-review mainly examines the effects of integrating the AI-based technology into flipped learning on students’ motivation and performance. As the research topic supported by artificial intelligence in the classroom is a relatively frontier topic, further exploration is needed. Exploring the integration of AI-based technology into flipped learning holds great potential for enhancing personalized learning experiences, automating tasks, and improving learning outcomes. This review concluded findings from a study between 2019 and 2023, articles were evaluated and screened using keyword flipped classroom and artificial technology, and duplicate papers were removed from the study. Finally, 12 empirical papers are selected according to the research focus. This paper summarizes the research methods, research fields, and data analysis. The results of this study show that in terms of technical challenges, the alignment of teaching objectives with AI techniques, ethical considerations, and human-computer interaction are important considerations for practitioners and researchers in integrating AI into the field of flipped learning. Addressing these limitations is critical to ensuring the successful implementation and ethical use of AI technologies. This review provides a foundation for future research to explore effective implementation strategies, evaluate the impact of AI integration on learning outcomes, and develop guidelines for the ethical and responsible use of AI in flipped learning environments.